Permasalahan yang dihadapi oleh Pendidikan Bahasa Jepang pada SMA/SMK di Bali - Oeinada, I Gede; Sari, Ida Ayu Laksmita; Putra, Anak Agung Anom Bintang Bayu; Kusuma, I Komang Rama (Humanis; Vol 27 No 1 (2023)DO - 10.24843/JH.2023.v27.i01.p09, 2023)
Following the implementation of the Merdeka Curriculum, Japanese language education at the high school / vocational level (SMA / SMK) in Bali faces a significant challenge. The lack of thorough understanding and communication caused the teachers to feel that the Merdeka Curriculum was less friendly to the Japanese language class hours in their schools. This article aims to describe the problems encountered in SMA / SMK in Bali related to Japanese language education not only in terms of policies in the form of the curriculum but also from the side of schools, teachers, and students. The data collection method uses a google survey form followed by an unstructured interview. The study in this article is included in the qualitative grounded theory research . Based on the research results, the problems faced by Japanese language education in SMA / SMK in Bali can be grouped into four categories: curriculum in SMA / SMK, school support , teacher ability, and student enthusiasm. It requires a correct understanding of the Merdeka Curriculum and good communication with policymakers in schools in order to overcome the problems faced.